Crisis múltiples del capitalismo global: mirando más allá de la esfera financiera - Fürst Weigand, Edgar (2013)
In the current debate on the crisis, main attention is directed to the financial sphere from the perspective of business cycle analysis (recession-recuperation). By contrast, this essay draws on the argument that there is virulent a grand crisis of the capitalist regime with multiple systemic-institutional features. In such interpretation are most important: (1) the (over)accumulation by dispossession, (2) the “financialization”, (3) the fragile hegemony of United States in the monetary world system.  After a brief crisis overview, the interpretative elements (1) – (3) are deepened in order to present finally some policies proposed as “solutions”.  The articles conclude with an outline of the open challenges and scenarios of change.